Minimal residual disease assessed by multi‐parameter flow cytometry is highly prognostic in adult patients with acute lymphoblastic leukaemia. (22nd October 2015) - Ravandi, Farhad; Jorgensen, Jeffrey L.; O'Brien, Susan M.; Jabbour, Elias; Thomas, Deborah A.; Borthakur, Gautam; Garris, Rebecca; Huang, Xuelin; Garcia‐Manero, Guillermo; Burger, Jan A.; Ferrajoli, Alessandra; Wierda, William; et al.
Summary: The prognostic value of minimal residual disease (MRD) assessed by multi‐parameter flow cytometry (MFC) was investigated among 340 adult patients with B‐cell acute lymphoblastic leukaemia (B‐ALL) treated between 2004 and 2014 using regimens including the hyperCVAD (hyperfractionated cyclophosphamide, vincristine, doxorubicin, dexamethasone, methotrexate, cytarabine) backbone. Among them, 323 (95%) achieved complete remission (CR) and were included in this study. Median age was 52 years (range, 15–84). Median white blood cell count (WBC) was 9·35 × 10 9 /l (range, 0·4–658·1 ×1 0 9 /l). MRD by MFC was initially assessed with a sensitivity of 0·01%, using a 15‐marker, 4‐colour panel and subsequently a 6‐colour panel on bone marrow specimens obtained at CR achievement and at approximately 3 month intervals thereafter. MRD negative status at CR was associated with improved disease‐free survival (DFS) and overall survival (OS) ( P  = 0·004 and P  = 0·03, respectively). Similarly, achieving MRD negative status at approximately 3 and 6 months was associated with improved DFS ( P  = 0·004 and P  < 0·0001, respectively) and OS ( P  = 0·004 and P  < 0·0001, respectively). Multivariate analysis including age, WBC at presentation, cytogenetics (standard versus high risk) and MRD status at CR, 3 and 6 months, indicated that MRD negative status at CR was an independent predictor of DFS ( P  < 0·05). Achievement of an MRD negative state assessed by MFC is an important predictor of DFS and OS in adult patients with ALL.